Exploring the efficacy of Mobile Assisted Language learning amongst Pakistani ESL learners: An attitudinal Study - Muhammad Mooneeb Ali, Dr Muhammad Asim Mahmood, Tayyaba Yasmeen (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Currently the latest technology driven devices and gadgets are becoming popular amongst masses. Amongst different devices mobile phones are the most important one for connectivity and other purposes in various contexts. Mobile phones are now also utilized for language learning purposes by students and teachers. This phenomenon is called Mobile assisted language learning (here onwards MALL). The current study is an investigation regarding the opinions of the Pakistani learners regarding the efficacy of mobile phone for language learning purposes in class rooms. The researchers aimed at finding out the perceptions of using mobile phone amongst higher secondary school students all around Pakistan in ESL class rooms. This research is important in exploring the fact that what opinion Pakistani students have about a commonly used technological trend in western world. The population comprised of 600 randomly selected intermediate level students from each provincial capital i.e. Karachi, Lahore, Peshawar, Gilgit and Quetta of Pakistan including federal capital Islamabad. Further a questionnaire comprised of 21 questions was asked from the respondents. The findings revealed that Pakistani students are welcoming this trend and they feel energetic, positive and enthusiastic in using mobile phone for learning purposes in and outside class rooms. This research has its practical implications.